Hafidh, THE LEVEL OF KNOWLEDGE OF HEALTH CARE WORKERS WITH THE LATENT TUBERCULOSIS - Aji Prasetyo, Hafidh Bagus; Adji, Raden Mas Soerjo; Setiawan, Andreas Arie; Pramudo, Setyo Gundi (RSUP Dr. Kariadi, 2021)
ABSTRACT Background : Pulmonary tuberculosis is a contagious infectious disease caused by the Mycobacterium tuberculosis. Health workers have an increased risk of contracting tuberculosis, because they are exposed to TB in their workplaces. The absence of hospital control measures against TB infection makes the risk factor becomes high. Health workers often make contact with TB sufferers. In a good body condition, although infected by TB germs, it does not manifest as a disease or called latent TB. However, latent TB sufferers still have the risk of being active in certain conditions, which then becomes a source of new TB transmission. Objective: This study aims to look at the level of knowledge of health workers towards the incidence of Latent TB in the Hospital. Method : The research method is cross-sectional using a sample of health workers who work in hospitals. The sample size of this study was 46 people using purposive sampling. This study has a variable Health worker knowledge about TB disease and Latent TB incidence. The method of data analysis using Chi Square Test. Result : The results were not significant between the level of knowledge and the incidence of Latent TB in health workers (p = 0.584). While the use of masks with the incidence of latent TB had a significant relationship (p=0,001). Conclusion : There is no significant relationship between the level of knowledge with the incidence of Latent TB in health workers. While the use of masks with the incidence of latent TB has a significant relationship. Keywords : Tuberculin Skin Test, Awareness, Incident, Workplaces.